Chordoma: Etiology, Pathogenesis, Diagnosis, Treatment - Julia V. Travkina; Tatiana N. Zhevak; Peter F. Litvitsky (Вопросы современной педиатрии, 2018)
The lecture analyzes modern knowledge about etiology, key mechanisms of pathogenesis, clinical manifestations, types, diagnostic methods and treatment strategy of chordoma (tumor from notochordal cells). To assess the retention of the lecture material, a case problem and multiple-choice test questions are given.